Batch and semi-batch reactors : practical guides in chemical engineering - Worstell, Jonathan (Waltham, MA ; Butterworth-Heinemann/Elsevier, 2015)
'A concise and practical guide to fixed-bed reactors and their application in the chemical processing industry. [...] Batch and Semi-batch Reactors covers chemical kinetic investigations conducted in batch reators, as well as the fundamental features of batch and semi-batch reators. It discusses upscaling and downscaling both reactors, using analytic methods based on conservation laws and empirical methods based on experimental data. Batch and Semi-batch Reactors concludes with a review of their operating features. This text is ideal for any engineer who is new to working with batch or semi-batch reactors and needs to know the basics quickly.'--
Introduction -- Batch reactors -- Scaling batch reactors -- Semi-batch reactors -- Batch and semi-batch operations.
Keywords: Chemical reactors; Chemical engineering -- Handbooks, manuals, etc